2020
DOI: 10.1021/acsomega.9b03957
|View full text |Cite
|
Sign up to set email alerts
|

Novel Inulin Electrospun Composite Nanofibers: Prebiotic and Antibacterial Activities

Abstract: Inspired by the rampant digestive disorders and the vast bacterial infections, this study aimed at fabricating nanofibers made of inulin/polyvinyl alcohol (PVA) composite nanofibers (CNFs) using the electrospinning technique and testing their prebiotic and antibacterial activities. The inulin/PVA CNFs were tested for prebiotic activity with Lactobacillus species while Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) were used to assess the antibacterial potentiality. During the fabrication of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The high thermal stability of inulin and quercetin has been reported. For example, Wahbi [ 49 ], analyzed the thermal behavior of an inulin extract that started to decompose at ≈235 °C [ 49 ], and of raw inulin at 215 °C [ 50 ]. On the other hand, the reported thermal degradation of quercetin was observed between 245 and 390 °C [ 36 ], which is similar to the results obtained in the present project ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high thermal stability of inulin and quercetin has been reported. For example, Wahbi [ 49 ], analyzed the thermal behavior of an inulin extract that started to decompose at ≈235 °C [ 49 ], and of raw inulin at 215 °C [ 50 ]. On the other hand, the reported thermal degradation of quercetin was observed between 245 and 390 °C [ 36 ], which is similar to the results obtained in the present project ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the reported thermal degradation of quercetin was observed between 245 and 390 °C [ 36 ], which is similar to the results obtained in the present project ( Figure 8 ). The observed higher temperatures range of NQs could be due to the physical and chemical interactions created between both inulin and quercetin [ 49 ]. No thermal data were found in the literature to directly compare the thermal behavior of NBs and NQs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that they significantly improved the activities against S. aureus biofilms and greatly inhibited their formation [ 59 ]. Wahbi et al demonstrated that composite nanofibers (CNF) of inulin/polyvinyl alcohol (PVA) had an increased antibacterial activity against E. coli and S. aureus [ 60 ]. Finally, a probiotic nanocomposite film based on carboxymethylcellulose (containing cellulose nanofiber) and inulin was developed.…”
Section: New Therapeutic Strategies: Combinatorial Treatmentsmentioning
confidence: 99%
“…[50,51] Varying these parameters, especially the voltage and feed rate, would result in differences in morphologies. [49,50] Voltage control impacts the nanofiber diameter, restriction of beading, and size distribution. Low voltage is often associated with highly beaded fibers of large diameters while an increase in voltage results in proper sequestration of polymer into narrow size distribution in the low-size region.…”
Section: Electrospun Nanofibersmentioning
confidence: 99%
“…Additionally, ambient parameters, humidity, and temperature of the electrospinner play a significant role in the resulting nanofibers [50,51] . Varying these parameters, especially the voltage and feed rate, would result in differences in morphologies [49,50] . Voltage control impacts the nanofiber diameter, restriction of beading, and size distribution.…”
Section: Electrospun Nanofibersmentioning
confidence: 99%